Reducing Antimicrobial Use by Implementing Evidence-Based, Management-Related Prevention Strategies in Dairy Cows in Switzerland - Gerber, Manuela; Dürr, Salome; Bodmer, Michèle (Frontiers in Veterinary Science, 2021)
The aim of this study was to reduce antimicrobial use (AMU) on dairy farms that implemented evidence-based management strategies. The study not only examined whether these strategies led to a reduction in AMU in practice, but also examined the influence of the level of their implementation on AMU. For data analysis, practice software recordings of the farm veterinarians were used. The AMU data of 50 farms with prevention strategies applied (intervention group, IG) over three years (2017-2019) and of 74 farms without prevention strategies (control group, CG) over two years (2018-2019) were analyzed. Project participation was supported with 500 Swiss francs (app. 545 USD) per farmer per year. The AMU was compared between the IG and CG using the treatment incidence. In December 2017/January 2018, the farmers of the IG had chosen at least one of the proposed 17 prevention strategies from one of three sectors, i.e. udder health, uterine health and/or replacement calf health. The prevention strategies, were developed in a standard operating procedure protocol and were discussed in detail with the farmers before the implementation. Forty-eight farms chose at least one udder strategy, 10 farms at least one uterine strategy and 37 farms at least one calf strategy. By choosing an udder health strategy or a uterine health strategy, the corresponding systemically administered AMU could be significantly reduced (p<0.04) in the IG compared with the CG. In addition, udder strategies that were well implemented led to a significant reduction (p=0.05) of intramammary "highest priority critically important antimicrobials (HPCIA)" (quinolones, cephalosporins 3rd and higher generation, macrolides and ketolides, glycopeptides and polymyxins). The level of implementation was significantly lower in 2019 compared to 2018 (p<0.05, Fisher's exact test). No significant reduction in AMU could be achieved for the calf sector. A reduction of AMU in dairy farms is possible by implementing evidence-based management-related prevention strategies. The level of implementation has only an influence on the consumption of HPCIA. The reduction of AMU in practice by means of evidence-based measures requires supportive human resources instead of financial support, because financial support for farmers seems not to motivate them sufficiently.